The complex interplay between psychosocial and biological factors in pregorexia nervosa — a rapid review - Vasiliu, Octavian (Frontiers in Psychology, 2023)
The importance of detecting eating disorders (EDs) during pregnancy can not be overemphasized, because of the major negative effects this pathology has on both maternal and fetal health. Based on a rapid review including primary and secondary reports, PN may still be considered an elusive diagnosis entity, that partially overlaps with other EDs, either well-defined, like anorexia nervosa, or still in search of their own diagnosis criteria, like orthorexia nervosa. Neurochemical and hormonal factors, psychological and social mechanisms, along with lifestyle changes create a very complex framework for clinicians interested in defining the typical features of pregorexia nervosa (PN). The personal history of EDs is considered one of the most important risk factors for PN. The core diagnosis diagnostic criteria for this entity are, so far, lack of gaining weight during pregnancy, an excessive focus on counting calories and/or intense physical exercising, with a secondary decrease minimal or lack of interest in the fetus’s health, lack of acceptance of the change in body shape during pregnancy, and pathological focus attention on for own body image. Regarding the treatment of PN, nutritional and psychosocial interventions are recommended but no specific therapeutic strategies for this disorder have been detected. Psychotherapy is considered the main intervention for pregnant women with associated EDs and mood disorders, as the pharmacological agents could have teratogenic effects or insufficient data to support their safety in this population. In conclusion, taking into consideration the methodological limitations of a rapid review, data supporting the existence of PN were found, mainly regarding tentative diagnostic criteria, risk factors, and pathophysiological aspects. These data, corroborated with the importance of preserving optimal mental health in a vulnerable population, e.g., pregnant women, justify the need for further research is needed for finding focused on finding specific diagnostic criteria for PN and specific targeted therapeutic approaches for this population.